2019
DOI: 10.1016/j.ijnurstu.2018.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Skin complications associated with vascular access devices: A secondary analysis of 13 studies involving 10,859 devices

Abstract: Background: Vascular access devices are widely used in healthcare settings worldwide. The insertion of a vascular access device creates a wound, vulnerable to irritation, injury and infection. Vascular access-associated skin complications are frequently reported in the literature, however very little evidence is available regarding the incidence and risk factors of these conditions to inform practice and technology development. Objectives: To estimate the incidence of vascular access-associated skin complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 35 publications
(28 reference statements)
0
13
0
1
Order By: Relevance
“…Participant characteristics: Upon enrolment, the ReN collected baseline data including: age; gender; height; weight; skin integrity (good, fair, poor) [17]; dominant hand; number of co-morbidities (0, 1, 2, 3, >3); primary admitting diagnosis and treatment duration; presence and type of current infections or wounds; blood type; and history of PIV and/or CVAD insertion.…”
Section: Data Sources/measurementmentioning
confidence: 99%
“…Participant characteristics: Upon enrolment, the ReN collected baseline data including: age; gender; height; weight; skin integrity (good, fair, poor) [17]; dominant hand; number of co-morbidities (0, 1, 2, 3, >3); primary admitting diagnosis and treatment duration; presence and type of current infections or wounds; blood type; and history of PIV and/or CVAD insertion.…”
Section: Data Sources/measurementmentioning
confidence: 99%
“…During long-term CVAD placement, the skin integrity surrounding catheter sites is a substantial challenge, as the skin is repeatedly in contact with disinfectants, dressings, etc. (Mimoz et al, 2015;Ullman et al, 2019). In 2017, a study provided practical references for clinical researchers and health workers to identify, prevent and treat CVAD-related skin lesions (Broadhurst et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that approximately 8% of hospitalized patients require CVADs during hospitalization, and more than 5 million central venous punctures are performed per year in the United States (Duwadi et al., 2019 ). Although catheter placement into the central vein is a common procedure performed in many clinical settings, severe insertion and retention complications associated with CVADs, such as bloodstream infections, skin lesions, phlebitis and thrombosis, are still prevalent (Jiang et al., 2020 ; Mimoz et al., 2015 ; Pu et al., 2020 ; Ullman et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, local infection accounted for the largest proportion in CASI type, and mechanical injury was relatively rare. Ullman et al [4] reported that in CASI with 10,859 vascular pathways (PICC, CVC, Port, etc. ), local infection or mechanical injury was relatively rare.…”
Section: Discussmentioning
confidence: 99%